Essays on food demand and supply in Bangladesh - Rahman, Kazi Tamim (Kansas State University, 2020)
The socio-economic and demographic conditions of Bangladesh have changed dramatically during the last three decades after economic and political reforms in 1991, which lead to change in food preferences both in rural and urban areas. Following the global trend of increasing commodity prices, the price hike in Bangladesh has raised policy concerns regarding the potential shifts in consumption patterns and welfare loss. Furthermore, the agricultural industry and the food supply in Bangladesh is highly susceptible to the effects of climate change and increased frequency of extreme weather events. The accurate and timely insights on food demand patterns in Bangladesh under the changing socio-economic scenarios can have important implications for food and nutritional security, price stability, poverty alleviation and appropriate import-export policy of the country. Policies on these issues cannot produce desired outcome without accurate estimation of consumer demand. However, despite the increasing need for improved understanding of food demand in Bangladesh, the literature in this area is relatively limited. The purpose of this dissertation is to provide insight on food demand and supply in Bangladesh by utilizing recent advancements in demand modeling and the latest and most complete data available on household food consumption in Bangladesh. The first essay examines welfare consequences of rising food prices in Bangladesh utilizing the Exact Affine Stone Index (EASI) demand model. Bangladeshi households experienced a sharp increase in food commodity prices during the last two decades especially in the period of 2007-2008. Inflation moved to two-digit level in 2007-08 and also in 2010-11 reaching 12.28% and 10.89% respectively, mostly driven by inflation in food prices. Estimating welfare impact of rising food price utilizing the prevalent demand models like the Almost Ideal Demand System (AIDS) and its’ family models may lead to biased estimate due to a number of practical limitations of these models. The EASI model has number of advantages over AIDS due to its flexibility in analysis of disaggregated consumer level data. In Essay 1, we utilize EASI model to estimate price and expenditure elasticities of 14 major food items using secondary data extracted from Household Income and Expenditure Survey (HIES) conducted by the Bangladesh Bureau of Statistics. The estimated elasticities are then used to evaluate the welfare consequences of rising food prices in Bangladesh. Welfare analysis based on both actual price change and simulated price change indicates that the welfare loss is the highest for lower income household. Further, the results indicate that the welfare loss of rural households was higher compared to that of urban households. The focus of the Essay 2 is on the analysis of pre-commitments in food demand in Bangladesh. Pre-committed demand is the portion of demand where the quantity demanded is not sensitive to changes in price or income. In the presence of pre-commitments, the demand is almost perfectly inelastic over the pre-committed portion of demand leading to biased estimates if it is not accounted for in modeling. The phenomenon of pre-committed demand for food has been more commonly observed in developing countries. Similar demand patterns are likely in Bangladesh with high proportion of low-income households and strong dependence on a range of staple food items by Bangladeshi households. Thus, in Essay 2, we utilize the generalized EASI (GEASI) demand model to estimate the demand elasticities of 14 major food items in Bangladesh by accounting for potential pre-commitments. The evidence of pre-committed demand is found in case of rice, pulse, vegetables and onion which accounts for 16.20%, 32.04%, 9.73% and 21.82% respectively. The new insights generated by the analysis in Essay 2 have important policy implications and can inform policy initiatives related to social safety net programs and food security of low-income households in Bangladesh. The Essay 3 focusses on forecasting supply and demand of rice in Bangladesh. Rice is not only the main staple food in Bangladesh but is also the single most important agricultural crop in terms of its contribution to national economy and its role in creating income and employment opportunities and ensuring food security. The analysis of rice supply and demand has always been at the center of policy makers attention in Bangladesh since the deficit tends to cause significant increase in price and resulting consumer welfare loss, while the surplus tends to result in price reductions negatively affecting farm profitability and household wellbeing in rural areas where the rice farming is the main source of income. Thus, the objective of this study is to forecast the supply and demand of rice with an aim to improve the understanding of potential deficit or surplus trends in the short- and long-term future. The analysis in Essay 3 utilizes ARIMA, Holt-Winter, and double exponential forecasting models. The findings reveal that both rice production and consumption will gradually increase in the short-run and in the long-run in Bangladesh. The forecasting results by ARIMA and Holt-Winter approaches show that there might be deficit in rice production in Bangladesh both in short-run and long-run with exceptions of rare surplus years. However, the results of double exponential approach indicate potential surplus in rice production both in the short-run and the long-run. Importantly, the deficits and surpluses are not large enough in magnitude to influence the price of the rice. The findings of the study would be useful for policy makers to formulate policies on rice production, distribution, export and import.
Keywords: Food demand and supply; Bangladesh; Forecasting; EASI demand model; GEASI demand model; Rice